2015
DOI: 10.1111/1467-6427.12079
|View full text |Cite
|
Sign up to set email alerts
|

Family therapists’ adult attachment styles and the therapeutic alliance

Abstract: Therapists' adult attachment style may affect their ability to form effective therapeutic alliances. An analysis of semi-structured interviews with eleven family therapists explored the relationship between their adult attachment styles, as assessed using a self-report measure, and their perceptions of the therapeutic alliance. A framework analysis was employed, using four dimensions of the therapeutic alliance: engagement in the therapeutic process, emotional connection to the therapist, safety within the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…However, the avoidant attachment style did not significantly contribute to the therapeutic alliance. Several studies, including Kandemir (2017), Sauer et al (2003), and Yusof and Carpenter (2016), have reported findings that are consistent with the those of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…However, the avoidant attachment style did not significantly contribute to the therapeutic alliance. Several studies, including Kandemir (2017), Sauer et al (2003), and Yusof and Carpenter (2016), have reported findings that are consistent with the those of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Prior to undertaking this study, my personal narrative was one of not being good enough (Lee & Littlejohns, 2007). A self-reflexive stance enabled me to reflect how my own attachment history encroached on my ability to connect with children and families in stressful sessions (Yusof & Carpenter, 2016). I noticed this in the interview with Charlie, as I felt uncomfortable when he was monosyllabic and my inner voice blamed myself (Rober, 2002(Rober, , 2008, believing I was not doing a good enough job to engage him.…”
Section: Discussionmentioning
confidence: 99%
“…I noticed this in the interview with Charlie, as I felt uncomfortable when he was monosyllabic and my inner voice blamed myself (Rober, 2002(Rober, , 2008, believing I was not doing a good enough job to engage him. Reflecting on this as I listened to his interview helped me understand how we both influenced one another (my preoccupied and his avoidant attachment styles), impacting on the therapeutic alliance (Dallos & Vetere, 2005Yusof & Carpenter, 2016). Rober (2008) reminds me to be aware of my feelings of comfort and discomfort in the session and to understand what this might mean, as this may create an opportunity to open up something new to explore.…”
Section: Discussionmentioning
confidence: 99%
“…For professionals who are not clinically trained in working with attachment repair, the risk of further damage is great and could result in avoidable trauma leading to additional negative outcomes. In addition, training programs for therapists or licensed clinicians require professionals to address personal issues that could interfere with a therapist's effectiveness (Suess et al, 2015; Yusof & Carpenter, 2016). Professionals untrained to use clinical interventions may not attend to these matters, and further, they are not subject to the same gatekeeping guidelines that are built into clinical training programs to keep individuals who are unsuitable for becoming therapists out of the field (Brear et al, 2008).…”
Section: Role Of the Family Keyworkermentioning
confidence: 99%